How Does LCL Height Influence Deep Convective Updraft Width?. Issue 13 (9th July 2021) - Mulholland, J. P.; Peters, J. M.; Morrison, H.
Abstract: Previous studies have hypothesized that the width of deep convection should positively scale with lifting condensation level (LCL) height. To evaluate this hypothesis, we analyzed idealized large‐eddy simulations with varying LCL heights and initial warm bubble widths in unsheared environments with comparable convective available potential energy. For a given initial warm bubble width, simulations with higher LCLs result in wider, deeper, and stronger cloudy updrafts compared to simulations with lower LCLs. Rising dry thermals in higher LCL simulations experience longer residence times within the sub‐cloud layer, and consequently entrain more conditionally unstable air and grow wider before reaching the LCL. The resulting cloudy updrafts are wider, deeper, and have faster vertical velocities because of a reduction in entrainment‐driven dilution of buoyancy, relative to lower LCL simulations. These results confirm the hypothesized positive relationship between LCL height and deep convective updraft width, and provide a physical explanation for this relationship. Plain Language Summary: Previous research has speculated that cumulonimbus clouds with a higher cloud base should be wider, all else being equal. We test this idea with cloud model simulations. This relationship between cloud base height and cloud width holds true in our simulations. We explain this behavior by differences in the width of regions of upward‐moving air below cumulonimbus clouds, in which they are rooted. When the cloud base is higher, this region of upward‐moving air grows wider before forming cloud compared to when the cloud base is lower. This results in wider and deeper clouds that have stronger upward motion than in the situations with a lower cloud base. Key Points: We find positive relationships between lifting condensation level (LCL) height and updraft width, depth, and vertical velocities among simulations with similar convective available potential energy (CAPE) These relationships are explained by ascending sub‐cloud dry thermals growing wider when the LCL is high, compared to when the LCL is low Wider sub‐cloud dry thermals lead to wider, less dilute, and stronger moist updrafts compared to narrower sub‐cloud dry thermals